2022
DOI: 10.3389/fonc.2022.981059
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lymph node metastasis in patients with breast invasive micropapillary carcinoma based on machine learning and SHapley Additive exPlanations framework

Abstract: Background and purpose: Machine learning (ML) is applied for outcome prediction and treatment support. This study aims to develop different ML models to predict risk of axillary lymph node metastasis (LNM) in breast invasive micropapillary carcinoma (IMPC) and to explore the risk factors of LNM.Methods: From the Surveillance, Epidemiology, and End Results (SEER) database and the records of our hospital, a total of 1547 patients diagnosed with breast IMPC were incorporated in this study. The ML model is built a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Therefore, model performances can be overly optimistic, and can underperform when evaluated on unseen real-world data. That can be seen in the results reported by Jiang et al, where the XGBoost AUC on the test set was 0.81, which dropped to 0.70 when evaluated on an external validation cohort [ 47 ]. Moreover, one systematic review has shown that in DL radiology applications, validation scores will demonstrate a modest to substantial decrease when compared to internal performance [ 54 ].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, model performances can be overly optimistic, and can underperform when evaluated on unseen real-world data. That can be seen in the results reported by Jiang et al, where the XGBoost AUC on the test set was 0.81, which dropped to 0.70 when evaluated on an external validation cohort [ 47 ]. Moreover, one systematic review has shown that in DL radiology applications, validation scores will demonstrate a modest to substantial decrease when compared to internal performance [ 54 ].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 92%
“…One other study that evaluated ML methods only on breast cancer patients with invasive micropapillary carcinoma also had XGBoost as the best performing algorithm [ 47 ]. As determined by Shapley values, tumor size, and patient age were the two most important features.…”
Section: Studies Using Clinicopathological Features For Breast Cancer...mentioning
confidence: 99%
See 1 more Smart Citation
“…If we can develop a tool or model to predict the probability of mortality, it would be helpful to urge MBC patients to receive timely profession examination or treatment. In recent years, ML models have also been widely applied to predict survival or lymph node metastasis of breast cancer [23,35,36]. However, it has not been used to predict the distant metastasis risk of MBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…To intuitively understand the nature of the ML model with the feature of 'black-box' , the SHAP framework was introduced into this study to interpret the optimal ML model. Its interpretability performance has been validated in many models [21][22][23]. The SHAP framework could present global (e.g., summary plot) and local (e.g., force plot) interpretability plots based on SHAP values.…”
Section: The Explanation Of ML Modelsmentioning
confidence: 99%